Characteristics and Well Practices About Teaching Learning Process in Graduate Programs According to the Stakeholders (2023)
This study analyzes some determinants of teaching quality in Master's degree programs in Engineering, taken into account the point of view of students, in a Colombian university, using mixed (quantitative-qualitative) research techniques. The study aggregates factors that are important in such contexts as the institutional environment, theory-practice balance in courses, professor who has experience as researcher, students’ characteristics as well as their previous experiences, and tutoring. These factors are interrelated. In this sense, issues such as professors’ methodology and research experience are highly valued by the students, whereas professors stress the importance of their work as a peer, that is to say being recognized in the academic community as a reference in the discipline. The implications of this research is to know and develop new methodologies to evaluate teacher’s performance but this time in graduate level, topic with fewer evidences than those in undergraduate level